Imprensa e educação : a difusão das práticas escolares no jornal Gazeta Socialista (1948-1958) - Santos, Geane Corrêa dos (2009)
This work has the objective of checking how education in Sergipe was publicized through the newspaper Gazeta Socialista , between the years of 1948 and 1958, observing, how school cultural practices; professional education and schools instituitions were shown.. Theoretical support New Culture History was marked by dialogue with Roger Chartier (1992, 1990, 2002); Jacques Le Goff (2002) and Peter Burke (1992, 1989) to apprehend the elements of historiografic thought. It used education‟s historiografic authors to understand the process of development, between Eliane Marta Teixeira Lopes and Ana Maria de Oliveira Galvão (2001) and Vidal and Faria Filho (2005). The press was understood by Sodré (1999); Martins (2001) and Luca and Martins (2007), Guaraná (1925), Araújo (1993) Nascimento e Freitas (2001) and Nunes (1983). The work noticed during the analysed period the news highlighted vocational teatching, the school‟s celebrations, estudants brings, relevant for socity and worried very much with activy of Industrial Aracaju School and Rui Barbosa Education Institute, it valued the professional of education and protested against the bad situation of primary school.